Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 172953 by Mathspace last updated on 03/Jul/22

find ∫_0 ^1 (√(1−x^4 ))lnx dx

find011x4lnxdx

Answered by Ar Brandon last updated on 03/Jul/22

Ω=∫_0 ^1 (√(1−x^4 ))lnxdx , x=t^(1/4)       =(1/(16))∫_0 ^1 t^(−(3/4)) (√(1−t))lntdt=(1/(16))∙(∂/∂α)∣_(α=(1/4)) ∫_0 ^1 t^(α−1) (√(1−t))dt      =(1/(16))∙(∂/∂α)∣_(α=(1/4)) β(α, (3/2))=(1/(16))∙(∂/∂α) ((Γ(α)Γ((1/2))(1/2))/(Γ(α+(3/2)))) _(α=(1/4))       =((√π)/(32))∙(((Γ′(α))/(Γ(α+(3/2))))−((Γ(α)ψ(α+(3/2)))/(Γ(α+(3/2)))))_(α=(1/4)) =((√π)/(32))(((Γ((1/4))ψ((1/4))−Γ((1/4))ψ((7/4)))/(Γ((7/4)))))      =((√π)/(32))∙((Γ((1/4)))/((3/4)Γ((3/4))))(ψ((1/4))−ψ((3/4))−(4/3))      =((√π)/(24))∙((Γ^2 ((1/4)))/(π(√2)))(−πcot((π/4))−(4/3))=−((√(2π))/(48π))(((3π+4)/3))Γ^2 ((1/4))

Ω=011x4lnxdx,x=t14=11601t341tlntdt=116αα=1401tα11tdt=116αα=14β(α,32)=116αΓ(α)Γ(12)12Γ(α+32)α=14=π32(Γ(α)Γ(α+32)Γ(α)ψ(α+32)Γ(α+32))α=14=π32(Γ(14)ψ(14)Γ(14)ψ(74)Γ(74))=π32Γ(14)34Γ(34)(ψ(14)ψ(34)43)=π24Γ2(14)π2(πcot(π4)43)=2π48π(3π+43)Γ2(14)

Commented by Ar Brandon last updated on 04/Jul/22

Commented by Ar Brandon last updated on 04/Jul/22

Commented by Tawa11 last updated on 06/Jul/22

Great sir

Greatsir

Answered by Mathspace last updated on 04/Jul/22

Υ=∫_0 ^1 (√(1−x^4 ))lnx dx changement  x^4 =t give  Υ=∫_0 ^1 (√(1−t))ln(t^(1/4) ).(1/4)t^((1/4)−1) dt  =(1/(16))∫_0 ^1 t^((1/4)−1) (1−t)^(1/2) lnt dt  let f(a)=∫_0 ^1 t^(a−1) (1−t)^(1/2) dt ⇒  f^′ (a)=∫_0 ^1 t^(a−1) (1−t)^(1/2) lnt ⇒  ∫_0 ^1 t^((1/4)−1) (1−t)^(1/2) lnt dt=f^′ ((1/4))  we have f(a)=B(a,(3/2))  =((Γ(a).Γ((3/2)))/(Γ(a+(3/2))))  Γ((3/2))=Γ((1/2)+1)=(1/2)Γ((1/2))=((√π)/2)  Γ(a+(3/2))=Γ(a+(1/2)+1)  =(a+(1/2))Γ(a+(1/2))  f(a)=((√π)/2)×((Γ(a))/(Γ(a+(3/2)))) ⇒  f^′ (a)=((√π)/2).((Γ^′ (a)Γ(a+(3/2))−Γ(a)Γ^′ (a+(3/2)))/(Γ^2 (a+(3/2))))  ⇒f^′ ((1/4))=((√π)/2).((Γ^′ ((1/4))Γ((1/4)+(3/2))−Γ((1/4))Γ^′ ((1/4)+(3/2)))/(Γ^2 ((1/4)+(3/2))))  =((√π)/2).((Γ^′ ((1/4))Γ((7/4))−Γ((1/4))Γ^′ ((7/4)))/(Γ^2 ((7/4))))  and Υ=(1/(16))f^′ ((1/4))

Υ=011x4lnxdxchangementx4=tgiveΥ=011tln(t14).14t141dt=11601t141(1t)12lntdtletf(a)=01ta1(1t)12dtf(a)=01ta1(1t)12lnt01t141(1t)12lntdt=f(14)wehavef(a)=B(a,32)=Γ(a).Γ(32)Γ(a+32)Γ(32)=Γ(12+1)=12Γ(12)=π2Γ(a+32)=Γ(a+12+1)=(a+12)Γ(a+12)f(a)=π2×Γ(a)Γ(a+32)f(a)=π2.Γ(a)Γ(a+32)Γ(a)Γ(a+32)Γ2(a+32)f(14)=π2.Γ(14)Γ(14+32)Γ(14)Γ(14+32)Γ2(14+32)=π2.Γ(14)Γ(74)Γ(14)Γ(74)Γ2(74)andΥ=116f(14)

Commented by Tawa11 last updated on 06/Jul/22

Great sir

Greatsir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com